Right to the City: The Forum of Public Policy Councils’ experience in the interior of Minas Gerais - Batista Corrêa da Costa, Márcia Helena; Meire Guimarães, Sandra; Castro, Bruna Laís (Guará Journal, 2018)
The experience reported in this article was developed from the articu-lation between research and university extension, having as object the project "Political Participation and Right to the City". The central objective was to create situations of interlocution of the University with the organized social segments, acting in Councils and other modalities of associativism, with a view to favoring the understanding of these actors on the right to the city. The reference of the discussions was the Urban Reform present in Law n. 10.257 / 2001, the City Statute (ver a observação acima, neste caso acrescentar a conjunção se for outra obra), in order to promote the maturation of channels for dialogue between civil society and local public authorities, stimulating processes of political participa-tion aimed at consolidating the democratic management instruments of the city. The activities developed were successful, however, the depen-dence of these instances on the executive power impaired the continuity of actions and the autonomy sought for the councils in the conception and social control of policies.